HLA-G 14 bp deletion/insertion polymorphism in celiac disease. - Fabris, Annalisa; Segat, Ludovica; Catamo, Eulalia; Morgutti, Marcello; Vendramin, Anna; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Nonclassical major histocompatibility class I HLA-G antigen is a tolerogenic molecule that inhibits lytic activity of natural killer (NK) cells and cytotoxic T lymphocytes. Because of its immunomodulatory and tolerogenic properties, HLA-G molecules may have a role in celiac disease (CD). We analyzed the HLA-G 14 bp deletion/insertion polymorphism, known to have a functional effect on mRNA stability, in a group of 522 CD patients, stratified for the presence of HLA-DQ2 genotype, and 400 healthy individuals to evaluate the possible effect of the polymorphism on the risk to develop the disease. METHODS: HLA-G 14 bp deletion/insertion polymorphism (rs1704) was detected by polymerase chain reaction and double-checked by direct sequencing. RESULTS: The 14 bp inserted (I) allele and the homozygous I/I genotype were significantly more frequent in CD patients than in healthy controls. The presence of I allele was associated with an increased risk of CD (OR 1.35) and the effect of I allele was consistent with a recessive genetic model (P<0.001). CONCLUSIONS: Our results also indicate that the effect of the HLA-G D/I polymorphism is restricted for HLA-DQ2, and not simply due to the presence of linkage disequilibrium with the major known risk factor; moreover we found that the presence of the I allele confers an increased risk of CD in addition to the risk conferred by HLA-DQ2 alone and that subjects that carry both DQ2 and HLA-G I alleles have an increased risk of CD than subjects that carry DQ2 but not the I allele.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; Confidence Intervals; Female; Genetic Predisposition to Disease; Genotype; Histocompatibility Antigens Class I; HLA Antigens; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Mutagenesis, Insertional; Odds Ratio; Polymerase Chain Reaction; Polymorphism, Genetic; Reference Values; RNA Stability; Sequence Deletion; Young Adult

The missense variation Q705K in CIAS1/NALP3/NLRP3 gene and an NLRP1 haplotype are associated with celiac disease. - Pontillo, Alessandra; Vendramin, Anna; Catamo, Eulalia; Fabris, Annalisa; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Celiac disease (CD) is a multifactorial common disorder with several susceptibility loci. Variations in the NALP1/NLRP1 and NALP3/NLRP3 genes have been reported to confer risk for several autoimmune conditions. We hypothesized that polymorphisms in these genes, due to their role in innate immunity and inflammatory processes, may affect susceptibility to CD. METHODS: Two single-nucleotide polymorphisms (SNPs) in NLRP1 (rs12150220, rs2670660) and two SNPs (rs10754558, rs35829419) in NLRP3 genes were genotyped in 504 CD Italian patients and 256 healthy controls. RESULTS: The minor A allele of NLRP3 rs35829419 (Q705K) polymorphism appeared to exert a protective role against the development of CD (P=0.029; odds ratio (OR)=0.56). Moreover, a particular NLRP1 haplotype was associated with predisposition to CD (P=0.003; OR=1.38), even more when present in combination with the rs35829419 major C allele (P=0.002; OR=1.42). CONCLUSIONS: We hypothesized that the deregulation of CIAS1/NALP3/NLRP3 and NALP1/NLRP1 inflammasomes could have a role in CD pathogenesis.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Apoptosis Regulatory Proteins; Carrier Proteins; Celiac Disease; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Glutamine; Haplotypes; Humans; Inflammasomes; Italy; Lysine; Male; Mutation, Missense; Polymorphism, Single Nucleotide